(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Technology adoption enhances human resource capabilities to contribute to organizational efficiency and competitive advantage. This study examined how electronic human resources management (e-HRM) practices, moderated by digital literacy, improve organizational performance in North-Western Nigeria. The study was guided by the Technology Acceptance Model, complemented by Resource Base View and Human Capital Theories. Using a cross-sectional survey, data were collected by questionnaire from 592 employees of seven federal universities in North-Western Nigeria. A total sample size of 448 respondents was used. Descriptive and inferential statistics tests using the Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the data. The findings revealed that digital literacy, e-communication and e-performance appraisal have positive and statistically significant effects on organizational performance, while e-recruitment has a negative statistically significant effect on organizational performance. This suggests that the existing e-recruitment systems may not be adequately developed, properly utilized, or effectively integrated into institutional recruitment processes. Also, digital literacy has a significant moderating role in the relationship between e-performance appraisal, e-communication, and organizational performance. However, digital literacy exhibited negative but significant moderating influence on the relationship between e-recruitment and organizational performance. This would imply that possessing digital competencies alone is insufficient to guarantee improved recruitment outcomes when the supporting technological infrastructure and recruitment systems are ineffective Based on these findings, the study recommends that the management of federal universities should establish technical support and mentoring systems to ensure staff continuously improve their digital capabilities and adapt to evolving technologies.